Cellular depletion of major cathepsin proteases reveals their concerted activities for lysosomal proteolysis - Gallwitz, Lisa; Bleibaum, Florian; Voss, Matthias; Schweizer, Michaela; Spengler, Katharina; Winter, Dominic; Zöphel, Frederic; Müller, Stephan; Lichtenthaler, Stefan; Damme, Markus; Saftig, Paul (Cellular and molecular life sciences : CMLS, 2024)
Proteins delivered by endocytosis or autophagy to lysosomes are degraded by exo- and endoproteases. In humans 15 lysosomal cathepsins (CTS) act as important physiological regulators. The cysteine proteases CTSB and CTSL and the aspartic protease CTSD are the most abundant and functional important lysosomal proteinases. Whereas their general functions in proteolysis in the lysosome, their individual substrate, cleavage specificity, and their possible sequential action on substrate proteins have been previously studied, their functional redundancy is still poorly understood. To address a possible common role of highly expressed and functional important CTS proteases, we generated CTSB-, CTSD-, CTSL-, and CTSBDL-triple deficient (KO) human neuroblastoma-derived SH-SY5Y cells and CTSB-, CTSD-, CTSL-, CTSZ and CTSBDLZ-quadruple deficient (KO) HeLa cells. These cells with a combined cathepsin deficiency exhibited enlarged lysosomes and accumulated lipofuscin-like storage material. The lack of the three (SH-SY5Y) or four (HeLa) major CTSs caused an impaired autophagic flux and reduced degradation of endocytosed albumin. Proteome analyses of parental and CTS-depleted cells revealed an enrichment of cleaved peptides, lysosome/autophagy-associated proteins, and potentially endocytosed membrane proteins like the amyloid precursor protein (APP), which can be subject to endocytic degradation. Amino- and carboxyterminal APP fragments accumulated in the multiple CTS-deficient cells, suggesting that multiple CTS-mediated cleavage events regularly process APP. In summary, our analyses support the idea that different lysosomal cathepsins act in concert, have at least partially and functionally redundant substrates, regulate protein degradation in autophagy, and control cellular proteostasis, as exemplified by their involvement in the degradation of APP fragments.